2019
DOI: 10.21608/jabps.2019.15621.1054
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches for Enhancement of Curcumin Aqueous Solubility and Dissolution rate

Abstract: Curcumin (CUR) is a nature polyphenolic phytoingredient. CUR showed anti-inflammatory, anti-oxidant, anti-fungal and anticancer activities. The therapeutic efficacy of CUR was limited due to its poor aqueous solubility, poor oral bioavailability. Poor solubility of drugs is the major challenge associated with formulation development. Therefore, the aim of present work was to enhance CUR aqueous solubility and dissolution rate using Physical mixture and its solid dispersion. CUR solid dispersions were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Solid dispersion allows for the reduction of drug particle size and crystallinity, increases surface area, and enhances wettability by the surrounding hydrophilic carriers [94][95][96]. Several studies showed that solid dispersion using hydrophilic polymers has significantly enhanced curcumin/analogues solubility and potentially improved their bioavailability and pharmacological potentials [87,[97][98][99][100][101][102][103]. In addition, the encapsulation of curcumin and curcumin analogues in nanoparticles (NPs) has been shown to be feasible and advantageous for overcoming the poor solubility issue and enabling delivery [56].…”
Section: Enhancing the Solubility And Bioavailability Of Curcumin And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Solid dispersion allows for the reduction of drug particle size and crystallinity, increases surface area, and enhances wettability by the surrounding hydrophilic carriers [94][95][96]. Several studies showed that solid dispersion using hydrophilic polymers has significantly enhanced curcumin/analogues solubility and potentially improved their bioavailability and pharmacological potentials [87,[97][98][99][100][101][102][103]. In addition, the encapsulation of curcumin and curcumin analogues in nanoparticles (NPs) has been shown to be feasible and advantageous for overcoming the poor solubility issue and enabling delivery [56].…”
Section: Enhancing the Solubility And Bioavailability Of Curcumin And...mentioning
confidence: 99%
“…The clinical use of curcumin/analogues was hindered by their hydrophobic nature and poor solubility in water, which negatively affected their bioavailability and pharmacological potentials [48]. The complexation of curcumin/analogues with various host compounds has been shown to be successful, with significantly increased solubility and bioavailability when using cyclodextrin [85][86][87][88][89], modified rice starch and polysaccharide complexes [90], pea protein [91], starch, and gelatine [92], as well as whey protein [91,93]. Solid dispersion approach has also been used to enhance the drug dissolution rate and solubility.…”
Section: Enhancing the Solubility And Bioavailability Of Curcumin And...mentioning
confidence: 99%
“…Weighed amount of nanocurcumin and their physical mixtures were placed in dissolution medium that consists of 500 ml of phosphate buffer pH 7.4 contains Tween 80 (0.1 % w/v) to maintain sink condition. Dissolution system was kept at 37 °C and agitated at constant rate of 50 rpm 19 . At specified time intervals of 5, 15, 30, 60, 90, and 120 minutes, aliquots of 5 mL were withdrawn and filtered by membrane disc filter (0.45µm).…”
Section: In-vitro Dissolution Studiesmentioning
confidence: 99%